The chronology of Brexit and UK monetary policy - Martin Geiger; Jochen Güntner (Johannes Kepler University of Linz, Department of Economics, 2022)
The outcome of the referendum on the UK's membership of the European Union in June 2016 was largely unanticipated by politicians and pundits alike. Even after the "Leave" vote, the uncertainty surrounding the withdrawal process might have affected the UK economy. We draw on an official list of political events published by the House of Commons Library and daily data on UK stock prices, exchange rates, and economic policy uncertainty to construct a novel instrument for Brexit shocks. Including a monthly aggregate of this time series into a vector-autoregressive model of the UK economy, we find that Brexit shocks were quantitatively important drivers of the business cycle in the aftermath of the referendum that lowered gross domestic product, consumer confidence, and monetary policy rates while raising CPI inflation. A counterfactual experiment, in which we shut down the endogenous response of UK monetary policy to Brexit shocks, reveals that the Bank of England fended off a stronger contraction of output in 2016 and 2018.
Keywords: E02; E31; E32; E44; E58; F15; 330; Brexit; business cycle; economic policy uncertainty; high-frequency identification; monetary policy